Does language make people more prosocial? The influence of Mandarin proficiency on donation behavior - Wang, Qiang; Yu, Laihui; Zhang, Ruilin (Frontiers in Psychology, 2023)
Both the effects of language proficiency on individual outcomes, and the influencing factors of individual donation arouse wide concern, but researchers have hardly probed into the relationship between language proficiency and donation behavior. Using the data from the 2013 China General Social Survey (CGSS) and the binary logistic regression model as the benchmark model, this study empirically examines the influence and mechanism of language proficiency on donation behavior. It is revealed that Mandarin proficiency has a significant positive influence on individual donation behavior. According to the results of the variable substitution practice and the instrumental variable regression based on the two-stage least square model, the above conclusion remains robust. The heterogeneity test shows that Mandarin proficiency of male, southern and rural residents has more obvious impact on donation behavior. The multiple intermediary effect test indicates that perceived social responsibility and subjective social status partially mediate the relationship between Mandarin proficiency and donation behavior. Therefore, it indicates that language proficiency can make people more prosocial. This study contributes to the literature on donation behavior by examining the influencing mechanism of Mandarin proficiency on individual donation, and further the effects of language proficiency on individual outcomes, thereby providing theoretical and empirical support for the formulation of policies for the promotion of Mandarin and social donation in China.